“I am blaming you!” a case of Instagram’s news and moral panic of paracetamol consumption and children’s chronic kidney in Indonesia - Esfandani Peni Indreswari (Universitas Negeri Yogyakarta, 2023)
In terms of obtaining information people nowadays depend on the use of social media such as Instagram due to its ease of access. This routine has also changed media institutions in disseminating information, which is through their social media account for audience engagement and news distribution to survive in the information technology era. This research focuses on news dissemination through Instagram on health communication. It was found that such means through Instagram caused a moral panic among the audience. The health issue put in the spotlight of this research is paracetamol and chronic kidney in children, actively reported in October-November 2023 in Indonesia. The result showed moral panic materialized from incomplete information due to limited sentences. Other factors are building personal assumptions, blaming other parties, to distortion of information. This study uses the netnographic method on Instagram posts on @kompascom social media news account. The research is carried out in several stages consisting of investigation, interaction, immersion, and integration. This was conducted to see the culture of social media users of the news account. The data consisted of 162 comments from 6 news posts on @kompascom.